2020
DOI: 10.1108/aaaj-03-2019-3912
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between home and host logics of accountability in multinational corporations (MNCs): the case of the Fundão dam disaster

Abstract: PurposeThe major purpose of this paper is to answer the overarching questions of how multinational corporations (MNCs) address the multiple institutional logics of accountability and pressures of the field in which they operate and how the dominant logic changes and shifts in response to such pressures pre- and post-disaster situation.Design/methodology/approachIn-depth interpretive textual analyses of multiple longitudinal data sets are conducted to study the case of the Fundão dam disaster. The data sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 103 publications
(177 reference statements)
0
23
0
1
Order By: Relevance
“…Following from this, we make a second contribution in demonstrating the value of the concept of "institutional logics" for explaining the source of practice variations, recognizing that institutional contexts are characterized by the coexistence of multiple logics deriving from institutional orders. Drawing on institutional studies, accounting researchers have demonstrated how logics shape organizational responses (Safari et al, 2020;Golyagina, 2020;Yee, 2020;Conrath-Hargreaves and W€ ustemann, 2019). Yet, as Contrafatto et al (2019) note, relatively little attention has been paid to the likelihood that logics drive accounting practices, including sustainability reporting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following from this, we make a second contribution in demonstrating the value of the concept of "institutional logics" for explaining the source of practice variations, recognizing that institutional contexts are characterized by the coexistence of multiple logics deriving from institutional orders. Drawing on institutional studies, accounting researchers have demonstrated how logics shape organizational responses (Safari et al, 2020;Golyagina, 2020;Yee, 2020;Conrath-Hargreaves and W€ ustemann, 2019). Yet, as Contrafatto et al (2019) note, relatively little attention has been paid to the likelihood that logics drive accounting practices, including sustainability reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Interplays between logics and organizational responses, including practice variations, are well documented (Herremans et al, 2009;Ezzamel et al, 2012;Lander et al, 2013;Guerreiro et al, 2012;Conrath-Hargreaves and W€ ustemann, 2019;Malik and Nicholson, 2020). More recently, attention has focused on how organizations actively manage institutional complexity in the face of conflicting logics (Lepori and Montauti, 2020) and prioritize a particular logic over others when faced with disasters, instability and external pressures (Safari et al, 2020;Golyagina, 2020;Yee, 2020;Conrath-Hargreaves and W€ ustemann, 2019).…”
Section: Sustainability and Institutional Logicsmentioning
confidence: 99%
“…For example, content analysis may include textual or discourse analysis of CSR reports, public policy documents, and/or media press to triangulate empirical evidence (e.g. Safari et al, 2020). These also involve a combination of interview/case study and content analysis (e.g.…”
Section: Empirical Methodsmentioning
confidence: 99%
“…It is likely that MNCs will apply pluralist logic to discharge different social and environmental accountability to host (developing) countries where resource exploration and disasters occur, than to home countries where MNCs are from (Safari et al, 2020).…”
Section: International Influence and Globalisationmentioning
confidence: 99%
See 1 more Smart Citation